The retrofitting of historical masonry buildings with insufficient seismic resistance using conventional and non-conventional techniques. (March 2019) - Sayin, Baris; Yildizlar, Baris; Akcay, Cemil; Gunes, Baris
Abstract: Masonry structures, which differ from other types of structures in terms of construction techniques and the properties of load-bearing members, may have sufficient strength against vertical loads applying compressive stresses, but an insufficient level of strength against seismic loads involving tensile and shear stresses. Accordingly, it is necessary to seismically strengthen masonry structures to ensure their structural safety and to prolong their service life. The present study deals with the process of strengthening a historical masonry structure that was built in the late 19th century but was abandoned for many years after being used for various functions. The structure is currently planned to be refunctioned as a service building for a university through conventional and non-conventional techniques. The study is being planned in three phases, beginning with a research into the examined structure's historical process, followed by a seismic performance analysis and culminating in strengthening applications. In the building background survey, the functional changes that the structure has undergone since its construction are analyzed, and a numerical analysis is made to assess the seismic performance of the structure under earthquake loads in its current state. In the final stage, the strengthening applications for the load-bearing members of the structure are presented in detail. It is aimed for this study to serve as a representative application for the seismic retrofitting of historical masonry buildings. Highlights: It is performed that seismic performance of the masonry building built in Ottoman period. It is introduced that retrofitting techniques can be applied without destroying the originality of the building. Conventional and non-conventional strengthening applications are presented regarding the building.